A Method for Analyzing Fatty Acids in Cattle Hair, with Special Emphasis on Lauric Acid and Myristic Acid. Issue 11 (2nd October 2019) - Möller, Ramona; Nürnberg, Gerd; Albrecht, Elke; Ruth, Wolfgang; Brockmann, Gudrun A.; Dannenberger, Dirk
Abstract: This study is aimed at improving a protocol for measuring fatty acids in cattle hair with respect to sensitivity, repeatability, and speed to increase its applicability as a biomarker. For the investigation, 14 hair samples from German Holstein cows are used. Alternative methods for grinding the hair (mortar vs mill), lipid extraction (modified Folch vs kit extraction), and solvent evaporation before injection on a gas chromatograph (evaporated vs unevaporated extracts) are tested. Hair ground with a mill compared to that with a mortar has smaller particles and a higher concentration of total lipids after extraction ( p < 0.02). The kit used for lipid extraction is faster, and the amount of extracted total lipids and individual fatty acids, especially C12:0, is increased ( p  = 0.001). The analysis of unevaporated methyl ester extracts using gas chromatography (GC) analysis yields 5.8 and 1.3 higher amounts of C10:0 and C12:0, respectively, than those of evaporated extracts ( p < 0.001). According to the results, the protocol for determining fatty acids in cattle hair can be improved by grinding the hair with a mill, extraction of lipids with a kit, and direct loading of methyl ester extracts in a gas chromatograph. Practical Applications : The fatty acid profile of hair reflects the metabolic status of an animal for the previous 1–3 weeks, as these fatty acids are not influenced by diurnal and short‐term fluctuations. An improved protocol is developed that increases the throughput of fatty acid analysis and improves its applicability for practical use. For breeding and animal welfare, the analysis of cattle hair is possible for more efficient evaluation of the hair fatty acid profile as a robust biomarker in a larger animal population. Abstract : The optimized method for fatty acid analysis (solid arrows) in cattle hair increases the throughput compared to the existing method (dotted arrows). The higher speed and sensitivity improve the application of the hair fatty acid profile as a biomarker for energy availability in cows.